Diasporic diffusion and public policies: A Portuguese case study - Gonçalves, Andrea Nunes (2021)
With the re-orientation of the debate on migration and development, drifting many times away from the pre-conceived idea that the migrant chooses to exit over voice, the diaspora has been increasingly recognized as a potential actor on the governance of the homeland. Still, it has been systematically left out of the list of non-state actors involved in it – and characteristics as its in-betweenness and capacity to ask a producer of change, that make it a potential channel for policy diffusion remain largely unexplored in the literature. For many centuries, Portugal has been a country of emigration. This has resulted in the creation of a sizeable diaspora, with several Portuguese communities spread around the globe – so it becomes key to understand what the influence (if existing) of that diaspora is in the public policies of the homeland. Using the analytical framework proposed by Jörgens & Neves (2017) as a starting point, this thesis aims to analyze that influence, while filling the gap in the literature that connects diaspora and cross-national diffusion processes, especially in the Portuguese case. Standing as a more theoretical approach, the thesis paves the way for future empirical work, that allows to study the cross-national diffusion of public policies through the diaspora.